Two Hippocratic treatises on sight and on anatomy - Craik, Elizabeth M. (Studies in Ancient Medicine, 2006)
This book presents a new edition, with translation, introduction and commentary, of two short medical texts, both transmitted in the Hippocratic Corpus but surely neither by the historical Hippocrates. The two works differ considerably in nature and origins: On Sight (Part 1) is a sketchy surgical manual on eye afflictions, perhaps originating in the African continent, and On Anatomy (Part 2) is an allusive account of basic human anatomy, perhaps originating in north Greece. Each text is interpreted in its own right and in the wider context of Hippocratic and other medical writing. Both content and language are closely analysed. The conclusions reached impact on important questions relating to the origin, constitution and dissemination of the Hippocratic Corpus.